Designing Game Techniques and Specific Exercises for English Language Teaching and their Impact on Learning and Retention in 3rd -grade Elementary School Students - Fadakarzadeh, Esmaeil; Zare Shehneh, Mohammadtaghi; Mirshamsi, Hamideh; Mohammadi Ahmadabadi, Naser (International Journal of Psychosocial Rehabilitation, 2019)
The present study aimed to design game techniques, specific exercises for English language teaching and their effect on learning and retention of 3rd -grade elementary school students in Bafqh, Iran. For this purpose, the students firstly received a pre-test and six games were then designed to teach English. They included computer games, painting, flashcards, action games, cartoons, movies, and poetry, which received through two 45-minute sessions and their scores were compared with those traditional English teaching techniques. Learning and retaining the English language entail four skills including reading, writing, listening and speaking. The statistical population consisted of all 3rd -grade elementary school students in Bafqh city, Iran (N = 35).The covariance test was used to analyze the collected data and determine the relationships between the variables. Besides, the data were analyzed using SPSS software. According to the analysis of the research hypotheses, there are significant differences between the effectiveness of different types of games and exercise on learning and retention in 3rd-grade female students in Bafqh city, Iran